First record of the European pond turtle Emys orbicularis (Linnaeus, 1758) near Kočevje, SE Slovenia - Anja Pekolj; Behare Rexhepi; Tina Urek; Urban Dajčman; Katarina Drašler; Anamarija Žagar; Gregor Lipovšek; Marijan Govedič (Natura Sloveniae)
n/a